2019
DOI: 10.4067/s0717-75182019000200197
|View full text |Cite
|
Sign up to set email alerts
|

Tratamiento nutricional en úlceras por presión y úlceras venosas

Abstract: RESUMEN Las úlceras por presión (UPP) y úlceras venosas (UV) son frecuentes en adultos y adultos mayores. En Chile un 70% de las heridas crónicas corresponden a UV y la prevalencia de UPP en pacientes hospitalizados es de 28%. El objetivo de esta revisión es analizar la evidencia disponible respecto al tratamiento nutricional de individuos con UPP y UV. Estas úlceras tienen diferentes etiologías, pero ambas provocan un aumento de requerimientos energéticos, proteicos y de micronutrientes. La cicatrización de h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 39 publications
0
2
0
5
Order By: Relevance
“…Researchers have concluded that one of the main risk factors for VUs is a high BMI 6,28 . Patients with VUs in the lower limbs often have obesity or overweight.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have concluded that one of the main risk factors for VUs is a high BMI 6,28 . Patients with VUs in the lower limbs often have obesity or overweight.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have concluded that one of the main risk factors for VUs is a high BMI. 6,28 Patients with VUs in the lower limbs often have obesity or overweight. Adipose tissue is less vascularized and thus may decrease blood flow and nutrients to the wound.…”
Section: Discussion the Influence Of Nutrition Status On Vusmentioning
confidence: 99%
“…A localização também está relacionada à dificuldade de tratamento, visto que aquelas localizadas em proeminências ósseas estão em constante pressão e cisalhamento, dificultando a regeneração tecidual (18) . No que tange ao tipo de ferida, observa-se gravidade maior nas úlceras vasculares, por estarem ligadas à insuficiência venosa crônica e hipertensão crônica, o que traz implicações sistêmicas e locais que afetam a proliferação celular (19) .…”
Section: Discussionunclassified
“…Nota: (Kreindl, Basfi-fer, Rojas, & Carrasco, 2019) QUIZHPI AVILA, M. DEL R., TINTIN CRIOLLO, S. E., JÁCOME CHICA, J. S., & CRUZ SALGADO, G. V.…”
Section: Tratamientounclassified